2014
DOI: 10.1021/es404302m
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Trends in Freshwater Fish Tissue Mercury Concentrations Associated with Mercury Emissions Reductions

Abstract: Mercury (Hg) concentrations were monitored from 1999 to 2011 in largemouth bass (LMB) and yellow perch (YP) in 23 lakes in Massachusetts USA during a period of significant local and regional Hg emissions reductions. Average LMB tissue Hg concentration decreases of 44% were seen in 13 of 16 lakes in a regional Hg "hotspot" area. YP in all lakes sampled in this area decreased 43% after the major emissions reductions. Comparative decreases throughout the remainder of the state were 13% and 19% for LMB and YP resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…If this analysis is valid, then reductions in U.S. emissions since that time could contribute to reductions in atmospheric mercury in the region. Recent analyses have suggested that reductions in U.S. emissions have indeed led to observable, decreasing trends in environmental mercury concentrations at many sites in the Great Lakes and surrounding regions (Castro and Sherwell, 2015;Giang and Selin, 2016;Hutcheson et al, 2014;Sunderland et al, 2016;Weiss-Penzias et al, 2016;Zhang et al, 2016), lending credibility to the results presented here.…”
Section: Discussionsupporting
confidence: 80%
“…If this analysis is valid, then reductions in U.S. emissions since that time could contribute to reductions in atmospheric mercury in the region. Recent analyses have suggested that reductions in U.S. emissions have indeed led to observable, decreasing trends in environmental mercury concentrations at many sites in the Great Lakes and surrounding regions (Castro and Sherwell, 2015;Giang and Selin, 2016;Hutcheson et al, 2014;Sunderland et al, 2016;Weiss-Penzias et al, 2016;Zhang et al, 2016), lending credibility to the results presented here.…”
Section: Discussionsupporting
confidence: 80%
“…Instead, mean fish Hg concentrations were found to be slightly higher in the period 2005-2010 than in 1974-1981, and were significantly so in northern pike. Such divergent results were also reported in fish Hg in four small lakes within a national park in northern Minnesota Science of the Total Environment xxx (xxxx) xxx-xxx (Brigham et al, 2014) and throughout the State of Massachusetts (Hutcheson et al, 2014) in the USA. Whereas the majority of these lakes showed a decreasing trend in fish Hg between~2000 and~2010, a smaller set of lakes showed an increasing or no trend.…”
Section: Case Study 1: Fish and Birds In Lakes And Coastal Waters Of mentioning
confidence: 79%
“…These results are in line with those recently reported in Michigan’s Upper Peninsula 48 . Substantial and rapid response of fish contamination to reduced emissions have been observed near emissions sources 7274 . However, the relatively lower policy impacts in remote areas (see Section 3.2) are likely to considerably prolong the time required to see substantial decreases in fish Hg concentrations.…”
Section: Resultsmentioning
confidence: 99%